Venture philanthropy strategies to support translational research : workshop summary - Hanson, Sarah L. (Sarah Lynn), 1980-; Nadig, Lori; Altevogt, Bruce M. (Online access: NCBI NCBI Bookshelf., 2009)
"Many voluntary health organizations fund translational research. An increasing number of these organizations are looking at venture philanthropy as a critical way to advance their missions of helping patients and working to cure disease. A wide range of participants gathered on October 3, 2008 at the Beckman Center of the National Academies of Science for a workshop titled "Venture Philanthropy Strategies Used by Patient Organizations to Support Translational Research." Participants with experience in venture philanthropy shared their experiences and lessons learned in order to improve efficiency and effectiveness in translational research."--Executive summary